2020
DOI: 10.22319/rmcp.v11i3.5157
|View full text |Cite
|
Sign up to set email alerts
|

Crecimiento de corderos y productividad en ovejas Pelibuey mantenidas bajo condiciones tropicales de producción

Abstract: El objetivo fue evaluar los efectos de época y año de nacimiento, tipo de parto, sexo y número de parto sobre el crecimiento predestete y la productividad de las ovejas en ovinos de raza Pelibuey que producen bajo un sistema semi-extensivo en el trópico húmedo de México. Se usaron datos de 323 ovejas Pelibuey a partir de registros de producción de 2011-2017. Se evaluaron los pesos al nacimiento (PN) y al destete (PD, a 60 d), así como los pesos de camada al destete (PCD). Adicionalmente, se evaluó prolificidad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…Other reports in the Mexican tropics have found higher values, such as 1.55, 1.71, 1.50, 1.56 lambs, respectively. (7,11,13,19) Notter et al (20) in Katahdin under USA conditions reported 1.82 lambs, showing the greatest maternal advantage of the breed for this trait, which is slightly higher than those obtained here. In addition, in the present study the B breed did not show good prolificacy as was expected, being the best the RK and Katahdin × Blackbelly (K × B) groups with 1.44 lambs.…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…Other reports in the Mexican tropics have found higher values, such as 1.55, 1.71, 1.50, 1.56 lambs, respectively. (7,11,13,19) Notter et al (20) in Katahdin under USA conditions reported 1.82 lambs, showing the greatest maternal advantage of the breed for this trait, which is slightly higher than those obtained here. In addition, in the present study the B breed did not show good prolificacy as was expected, being the best the RK and Katahdin × Blackbelly (K × B) groups with 1.44 lambs.…”
Section: Discussioncontrasting
confidence: 61%
“…(37) Other studies from the tropics of Mexico reported lower LWW values ranging from 16.50 to 19.10 kg. (7,9,13) In addition, as for the LLW the most reports are concerned about individual WW. (18,23,28,35) Based on their results, the last two authors and Nasrat et al (36) suggest that Katahdin and Dorper breeds could contribute favorably to improve LWW compared to Pelibuey and Blackbelly.…”
Section: Productivity Of Hair Breed Ewes In Southeastern Mexicomentioning
confidence: 99%
See 3 more Smart Citations